Development of Arabic Language Skills for Students at Syamsul Ulum Muhammadiyah Bandung Islamic Boarding School | Pengembangan Keterampilan Berbahasa Arab Santri Pondok Pesantren Syamsul Ulum Muhammadiyah Bandung - Siregar, Zulli Umri; Fauzia, Eva Lathifah; Fathurrahman, Yusuf (Ta’lim al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
This study aims to determine the development of language skills in Arabic skills training activities organized by the Syamsul Ulum Muhammadiyah Bandung Islamic Boarding School in collaboration with the Arabic Language Education Study Program at UIN Bandung. This research is qualitative research with a comparative descriptive method. The descriptive method is used to describe the satisfaction of the students and the input given regarding language skills training in 2021 and 2022 based on facts that occur in the field. Sources of research data are divided into two, namely primary and secondary. Primary data was obtained directly through the principal source, namely students as research subjects, through observation, interviews, and documentation techniques. Meanwhile, secondary data was obtained through literature studies related to the themes discussed in this study. Based on this explanation, the research steps were carried out as follows (1) data collection, (2) data presentation, (3) data analysis, and (4) concluding the analysis that has been carried out. The results showed that based on the results of the teacher assessment questionnaire filled out by students, the lowest percentage was 81% in 2021 and 83.8% in 2022 for mahÄrah istimÄâ€™ training, while the highest percentage in 2021 reached 85.4% and 87% for 2022 in training mahÄrah kalÄm. Students respond to suggestions and criticisms for teachers, which become material for discussion and evaluation for the study program so that they can provide better training in the future.